E-Transaction in Islamic Law and Indonesian Statutory Law Perspective | التعاقد الإلكتروني في الميزان الشرعي الإسلامي والقانون الوضعي الإندونيسي - Rusli Hasbi; Ahmad Khalimi (Al-Zahra : Journal for Islamic and Arabic Studies, 2018)
E-transactions have become a phenomenon that cannot escape human life, transactions using electronic devices, especially the internet, appear because of the rapid development of technology. The purpose of this study is to find out the extent of the requirements and pillars in e-transactions according to the perspective of Islamic law and Indonesian law -act number 11 of 2008 on Information and Electronic, also, act number 19 of 2016 as Amendment of the act later. In addition, it was also to reveal the lack of material law explaining matters related to electronic transactions, so that it needed the addition of material on related issues. The results of this article are that electronic transactions are legitimate and permissible in Islamic law but with conditions that do not contradict and meet the provisions stipulated in Islamic Sharia. furthermore, As for the positive Indonesian law, it is not clearly stated about the terms and conditions of electronic transactions, except that there are some elements relating to electronic transactions along with their definitions and explanations.